Effectiveness of Integrated Social and Behavior Change Communication Interventions in Mass Drug Administration Campaigns in Enhancing Knowledge, Perceptions, and Preventive Practices for Neglected Tropical Diseases in Jimma - Abdissa D; Kebede Y; Morankar S; Abraham G; Bulcha G; Shiferaw T; Berhanu N; Teshome F; Miecha H; Birhanu Z (Dove Medical Press, 2024)
Daba Abdissa,1 Yohannes Kebede,2 Sudhakar Morankar,2 Gelila Abraham,3 Gebeyehu Bulcha,4 Teshome Shiferaw,4 Nimona Berhanu,5 Firanbon Teshome,2 Hirpa Miecha,6 Zewdie Birhanu2 1Department of Biomedical Sciences, Jimma University, Jimma, Ethiopia; 2Department of Health, Behavior and Society, Jimma University, Jimma, Ethiopia; 3Department of Health Policy and Management, Jimma University, Jimma, Ethiopia; 4Jimma Zone Health Office, Oromia, Ethiopia; 5School of Pharmacy, Jimma University, Jimma, Ethiopia; 6Oromia, Regional Health Bureau, Oromia, EthiopiaCorrespondence: Daba Abdissa, Jimma University, Jimma, Ethiopia, Email dhaabaa4@gmail.comBackground: Despite control efforts, including mass drug administration (MDA), neglected tropical diseases (NTDs) continue to pose a significant public health threat, particularly in rural Ethiopia. Integrating social and behavior change communication (SBCC) into MDA is essential for success. This study aimed to evaluate the effectiveness of tailored SBCC integrated into MDA campaigns to enhance community knowledge, perception, and preventive behaviors regarding targeted NTDs in the Jimma, Ethiopia.Methods: A community-based study was conducted using a pre-test post-test design. A multistage sampling technique was employed for surveys, while for qualitative insights, purposive sampling was employed. SBCC interventions tailored to local needs were implemented. Changes in knowledge, perception, and practices were evaluated using Cohen's d. Additionally, a score for key outcome variables comparisons were made to examine variations based on socio-demographic factors, employing suitable statistical tests. Qualitative data were analyzed thematically using Atlas.ti 7.1.5.Results: The prevalence of SBCC exposure was 88.8%. The intervention had a more significant impact on improving knowledge and preventive practices related to Onchocerciasis (OC) compared to Soil-transmitted helminthes (STH). Specifically, most OC outcomes showed moderate to large effect sizes. In contrast, the effect on STH was more limited, with only knowledge of consequences improving moderately and preventive practices showing a small effect size. The mean score for OC preventive practices varied by educational level and sex, while the median score for STH perception varied among educational level and marital status. Additionally, score variation was observed across districts for all key outcome variables.Conclusion: The majority of the population was exposed to SBCC resulting in improvements in knowledge, perception, and preventive behaviors regarding OC and knowledge of consequences of STH and its prevention behavior. This highlights the importance of incorporating well-designed SBCC activities in to MDA campaigns to optimize the control and eventual elimination of targeted NTDs.Keywords: Knowledge, Perception, Preventive practices, Effectiveness, SBCC, Jimma, Ethiopia